Security Enhancement through the Allocation of a Unified Power Flow Controller (UPFC) in a Power Network for Congestion Management - Rajderkar, Vedashree P.; Chandrakar, Vinod K. (Engineering, Technology & Applied Science Research, 2023)
The electricity demand is continuously increasing, so a most efficient use of the current power system's capacity is desired. Flexible AC Transmission Systems (FACTSs), a recently developed transmission technology, are widely used to boost the power transfer ability of long-distance transmission line networks and to enhance the consistency of the transmission systems. The use of FACTS devices can lead to reduced flows on heavily loaded lines, targeted bus voltage levels, and better power network stability. In this study, an optimization method based on the optimal position of the Unified Power Flow Controller (UPFC) is suggested to boost system security. It is decided that the real power flow is the best place for the UPFC in this instance. The optimal placement during congestion has been determined using the Genetic Algorithm (GA) and the sensitivity to the useful power flow index. Congestion is produced on the network and system performance is evaluated. The proposed solutions are evaluated in the IEEE 30 bus network before being implemented in MATLAB. In the case of congestion, the security of the network is evaluated after connecting the UPFC. The effectiveness of the proposed solution was verified with the help of the Power World Simulator 16.0.